Bamboo film manufacturing process
By combining thalian bamboo powder with PLA/PCL and triethyl citrate glycerol, bamboo-based films with excellent mechanical properties and rapid degradation were prepared, which solved the problem of performance and environmental protection in the prior art, and achieved the following: Widely used in fields such as food packaging and agricultural coverage.
Patent Information
- Application Number
- CN202411478868.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-14
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of bamboo films, and in particular to a bamboo film manufacturing process. Background Art
[0002] In recent years, with the continuous improvement of environmental awareness and the increasingly serious problem of plastic pollution, the research and development of bio-based degradable film materials has attracted much attention. In this field, researchers have been committed to developing new materials that have both excellent performance and rapid degradation. At present, there are mainly two types of environmentally friendly film materials on the market: one is biodegradable polymer films represented by polylactic acid (PLA), polycaprolactone (PCL), etc.; the other is natural polymer films with starch, cellulose, etc. as the main components.
[0003] However, these existing technologies still have some difficult-to-overcome problems. Although biodegradable polymer films based on PLA have good mechanical properties and processing properties, their biodegradation rate is slow and their cost is high, which limits their large-scale application. Although films based on natural polymers have a fast degradation rate and low cost, their mechanical properties and barrier properties are often poor and difficult to meet the needs of practical applications. In addition, these two types of materials often require a large amount of chemical additives in the production process, which is to some extent contrary to the concept of environmental protection.
[0004] What is even more difficult is that existing technologies often fall into a dilemma when trying to improve both the mechanical properties and biodegradability of films. Improving mechanical properties usually requires increasing the crystallinity or cross-linking degree of the material, but this often reduces the biodegradation rate of the material. Conversely, improving biodegradability often leads to a decrease in mechanical properties. This contradiction between performance and degradability has always been a key issue that has troubled researchers. Summary of the invention
[0005] The present invention aims to solve the above technical problems by innovatively combining bamboo powder with biodegradable polymers and other functional additives to develop a new type of bamboo-based film material with excellent performance and rapid degradation characteristics. The present invention not only overcomes the contradiction between performance and degradability in the prior art, but also achieves the synergistic improvement of multiple technical indicators.
[0006] The present invention provides a bamboo film manufacturing process, comprising the following steps: (1) preparing bamboo powder; (2) preparing biodegradable auxiliary materials; (3) mixing the bamboo powder and the biodegradable auxiliary materials and extruding them; (4) blowing the extrudate into film; (5) cooling and stretching the formed film; (6) winding the stretched film; and (7) post-treating the wound film.
[0007] Preferably, the step (1) comprises: First, select 3-5 year old bamboo and remove the bamboo nodes and bamboo skin; Secondly, cut the bamboo into small pieces of 5-10cm in length; Then, use a wood slicer to cut the small segments into slices with a thickness of 1-3 mm; Next, dry at 60-80℃ for 8-12 hours to reduce the moisture content to 5-8%; Finally, the powder was crushed by a high-speed crusher and passed through a 1800-2200 mesh sieve to obtain bamboo powder with an average particle size of 5-10 μm.
[0008] Preferably, the step (2) comprises: (a) Add the following raw materials into the reactor in sequence: Polylactic acid (PLA) 15-25 parts by weight, Polycaprolactone (PCL) 10-20 parts by weight, 2-5 parts by weight of glycerol, 3-5 parts by weight of triethyl citrate; (b) First, PLA and PCL were heated to 170-180°C and stirred at 100-150 rpm for 30-40 minutes; (c) Next, cool to 140-150°C, add glycerol, and continue stirring for 10-15 minutes; (d) then adding triethyl citrate and stirring for 15-20 minutes; (e) finally cooling the mixture to room temperature and dicing to obtain biodegradable excipient granules.
[0009] Preferably, the step (3) comprises: Add 50-70 parts by weight of bamboo powder and 30-50 parts by weight of biodegradable auxiliary material particles into the feed port of a twin-screw extruder. Among them, the temperature distribution of the extruder from the feeding section to the discharging section is: 110℃, 120℃, 130℃, 140℃, 150℃, 160℃, The screw speed is set to 80-100rpm, The extrusion pressure is controlled at 10-15MPa. The material stays in the extruder for 3-5 minutes.
[0010] Preferably, the film blowing process parameters of step (4) include: die head temperature: 160-170° C., cooling ring temperature: 15-20° C., blow-up ratio: 2.5-3.5, and pulling speed: 10-15 m / min.
[0011] Preferably, the step (5) comprises: Use a multi-roll cooling system with a cooling roller temperature of 30-40°C. The cooled film passes through a traction roller with a stretch ratio of 1.2-1.5.
[0012] Preferably, the step (7) comprises: The rolled film is stored in a constant temperature and humidity chamber for 24-48 hours at a temperature of 23±2°C and a relative humidity of 50±5%; (b) the film is slit into the required width using a precision slitting machine at a slitting speed of 50-80 m / min; (c) Packaging the slit films.
[0013] Preferably, the polylactic acid PLA in the biodegradable auxiliary material has the following characteristics: Number average molecular weight Mn: 80,000-120,000 g / mol, Melting point: 150-170℃, Glass transition temperature (Tg): 55-65℃.
[0014] Preferably, the polycaprolactone PCL in the biodegradable excipient has the following characteristics: Number average molecular weight Mn: 70,000-90,000 g / mol, Melting point: 58-65℃, Glass transition temperature Tg: -60 to -65°C.
[0015] Preferably, the method further comprises performing quality control on the prepared film, specifically comprising: Test the film thickness, control it within the range of 20-50μm, and the thickness deviation shall not exceed ±5%; The tensile strength of the tested film should be no less than 20 MPa; The elongation at break of the test film should not be less than 200%; The water vapor transmission rate of the test film should not be higher than 100 g / (m²·24h); Conduct biodegradability tests and the degradation rate should reach more than 90% within 28 days under simulated composting conditions.
[0016] The beneficial effects of the present invention are: First, the present invention successfully combines bamboo powder, PLA and PCL to form a unique composite system. The cellulose structure in bamboo powder not only provides good mechanical strength, but also forms a complex network structure through special interaction with the polymer matrix, thereby significantly improving the overall performance of the film. This synergistic enhancement effect enables the film to have excellent mechanical properties while maintaining rapid biodegradability.
[0017] Secondly, the addition of glycerol and triethyl citrate in the present invention plays a key role. Glycerol, as a plasticizer, effectively improves the processing performance and flexibility of the material; while triethyl citrate significantly improves the compatibility of bamboo fiber and polymer matrix. The synergistic effect of these two additives not only optimizes the rheological properties of the material, but also improves the uniformity and overall performance of the film.
[0018] More importantly, the film of the present invention exhibits excellent selective barrier properties. This differentiated barrier effect on water vapor and oxygen is likely due to the fact that the addition of bamboo powder changes the arrangement of polymer chains and forms a special microscopic channel structure. This property is of great significance in the field of food packaging and other fields.
[0019] In terms of biodegradation, the film of the present invention not only maintains the characteristic of rapid degradation, but even slightly improves it in some cases. This may be because the bamboo powder provides an additional nutrient source for microorganisms, which accelerates the degradation process. This discovery provides a new idea for solving the problem of slow degradation of biodegradable materials.
[0020] In addition, the bamboo film of the present invention also exhibits unexpected thermal stability. The antioxidant components (such as lignin and bamboo flavonoids) contained in bamboo powder can act as stabilizers at high temperatures, which makes it possible to expand the application temperature range of bamboo film.
[0021] In general, the present invention has successfully found a balance between performance and environmental protection through clever material design and process optimization. It not only solves the key problems in the prior art, but also achieves synergistic improvement in performance in many aspects. This new bamboo-based film material has broad application prospects in the fields of food packaging, agricultural mulch, etc., providing an innovative solution to the problem of plastic pollution, and also opening up a new direction for the development and utilization of bio-based materials. DETAILED DESCRIPTION
[0022] The present invention will be further described below in conjunction with specific examples, but the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. In the following examples, if specific conditions are not specified, they are carried out according to normal conditions or conditions recommended by the manufacturer. The methods used are conventional methods known in the art unless otherwise specified, and the consumables and reagents used are commercially available unless otherwise specified. Unless otherwise specified, the professional and scientific terms used herein have the same meaning as those familiar to those skilled in the art. In addition, any method or material similar or equivalent to the recorded content may also be applied to the present invention.
[0023] Example 1 This embodiment provides a bamboo film manufacturing process, which makes full use of bamboo resources and combines biodegradable polymers to achieve the preparation of environmentally friendly film materials. The bamboo film manufacturing process of this embodiment includes the following steps: (1) Preparation of bamboo powder: First, select 3-year-old bamboo and remove bamboo nodes and bamboo skin. Secondly, cut the bamboo into small segments of 5 cm in length. Then, use a wood slicer to cut the small segments into thin slices with a thickness of 1 mm. Again, dry at 60°C for 8 hours to reduce the moisture content to 5%. Finally, use a high-speed grinder to crush and pass through an 1800 mesh sieve to obtain bamboo powder with an average particle size of 10 μm. Preferably, in an embodiment of the present invention, the specific surface area of the bamboo fiber is increased through a fine crushing process, which is conducive to the full mixing with the biodegradable auxiliary materials, thereby improving the uniformity and mechanical properties of the final film.
[0024] (2) Preparation of biodegradable excipients: In a reactor equipped with a heating and stirring device, the following steps are performed: First, 15 parts by weight of polylactic acid (PLA, number average molecular weight of 80,000 g / mol, melting point of 150°C, glass transition temperature of 55°C) and 10 parts by weight of polycaprolactone (PCL, number average molecular weight of 70,000 g / mol, melting point of 58°C, glass transition temperature of -60°C) are added. Second, the temperature is raised to 170°C, the stirring speed is set to 100 rpm, and maintained for 30 minutes to allow complete melting. Then, the temperature is lowered to 140°C, 2 parts by weight of glycerol is added, and stirring is continued for 10 minutes. Finally, 3 parts by weight of triethyl citrate is added and stirred for 15 minutes to allow it to be fully mixed. The mixture is cooled to room temperature and pelletized to obtain biodegradable excipient particles.
[0025] In the embodiment of the present invention, the combination of PLA and PCL provides good mechanical properties and controllable degradation rate. Glycerol as a plasticizer can improve the flexibility of the material, while triethyl citrate helps to improve the compatibility of bamboo fiber with the polymer matrix, thereby enhancing the overall performance of the film.
[0026] (3) Mixed extrusion: 70 parts by weight of bamboo powder and 30 parts by weight of biodegradable auxiliary material particles are added to the feed port of the twin-screw extruder. The temperature distribution of the extruder from the feed section to the discharge section is: 110°C, 120°C, 130°C, 140°C, 150°C, 160°C. The screw speed is set to 80rpm and the extrusion pressure is controlled to 10MPa. The material stays in the extruder for 3 minutes.
[0027] (4) Film blowing: The melt extruded from the die head immediately enters the film blowing machine. The parameters of the film blowing process are set as follows: die head temperature is 160 °C, cooling ring temperature is 15 °C, blow-up ratio is 2.5, and pulling speed is 10 m / min.
[0028] (5) Cooling and stretching: The film passes through a multi-roll cooling system, and the temperature of the cooling rollers is set at 30°C. The cooled film passes through a traction roller with a stretch ratio of 1.2.
[0029] (6) Winding: Finally, the film is wound up by the winding device, and the winding tension is controlled at 20N.
[0030] (7) Post-processing: The rolled film is stored in a constant temperature and humidity chamber for 24 hours at a temperature of 23°C and a relative humidity of 50%. Then, the film is slit into the required width using a precision slitting machine, and the slitting speed is controlled at 50 m / min. Finally, it is packaged in a clean environment and sealed with an antistatic polyethylene bag.
[0031] The bamboo film prepared by the above process has a thickness of 20μm, a tensile strength of 25 MPa, an elongation at break of 220%, and a water vapor permeability of 90 g / (m²·24h). The degradation rate within 28 days under simulated composting conditions reaches 95%. This film has good mechanical properties and barrier properties while maintaining excellent biodegradability, and is suitable for food packaging and agricultural covering.
[0032] Example 2 This embodiment provides another bamboo film manufacturing process, which further optimizes the performance of the film by adjusting the raw material ratio and processing parameters. The bamboo film manufacturing process of this embodiment includes the following steps: (1) Preparation of bamboo powder: First, select 5-year-old bamboo and remove the bamboo nodes and bamboo skin. Secondly, cut the bamboo into small sections of 10 cm in length. Then, use a wood slicer to cut the small sections into thin slices with a thickness of 3 mm. Thirdly, dry them at 80°C for 12 hours to reduce the moisture content to 8%. Finally, use a high-speed crusher to crush them and pass them through a 2200 mesh sieve to obtain bamboo powder with an average particle size of 5 μm.
[0033] In the embodiment of the present invention, the use of 5-year-old bamboo can obtain a higher cellulose content, thereby improving the strength of the film. At the same time, finer bamboo powder helps to improve the uniformity and surface smoothness of the film.
[0034] (2) Preparation of biodegradable excipients: In a reaction kettle, the following steps are performed: First, 25 parts by weight of polylactic acid (PLA, number average molecular weight of 120,000 g / mol, melting point of 170°C, glass transition temperature of 65°C) and 20 parts by weight of polycaprolactone (PCL, number average molecular weight of 90,000 g / mol, melting point of 65°C, glass transition temperature of -65°C) are added. Next, the temperature is raised to 180°C, the stirring speed is set to 150 rpm, and the mixture is kept for 40 minutes to allow it to be completely melted. Then, the temperature is lowered to 150°C, 5 parts by weight of glycerol is added, and stirring is continued for 15 minutes. Finally, 5 parts by weight of triethyl citrate is added and stirred for 20 minutes to allow it to be fully mixed. The mixture is cooled to room temperature and pelletized to obtain biodegradable excipient particles.
[0035] In this embodiment, the molecular weight of PLA and PCL is increased, which helps to improve the mechanical strength and thermal stability of the film. At the same time, the proportion of glycerol and triethyl citrate is increased, which further improves the flexibility and compatibility of the material.
[0036] (3) Mixed extrusion: 50 parts by weight of bamboo powder and 50 parts by weight of biodegradable auxiliary material particles are added to the feed port of the twin-screw extruder. The temperature distribution of the extruder from the feed section to the discharge section is: 110°C, 120°C, 130°C, 140°C, 150°C, 160°C. The screw speed is set to 100 rpm and the extrusion pressure is controlled to 15 MPa. The material stays in the extruder for 5 minutes.
[0037] (4) Film blowing: The melt extruded from the die head immediately enters the film blowing machine. The parameters of the film blowing process are set as follows: die head temperature is 170°C, cooling ring temperature is 20°C, blow-up ratio is 3.5, and pulling speed is 15 m / min.
[0038] (5) Cooling and stretching: The film passes through a multi-roll cooling system, and the temperature of the cooling roll is set at 40°C. The cooled film passes through a traction roll with a stretch ratio of 1.5.
[0039] (6) Winding: Finally, the film is wound up by the winding device, and the winding tension is controlled at 30N.
[0040] (7) Post-processing: The rolled film is stored in a constant temperature and humidity chamber for 48 hours at a temperature of 25°C and a relative humidity of 55%. Then, the film is slit into the required width using a precision slitting machine, and the slitting speed is controlled at 80 m / min. Finally, it is packaged in a clean environment and sealed with an antistatic polyethylene bag.
[0041] The bamboo film prepared by the above process has a thickness of 50μm, a tensile strength of 35 MPa, an elongation at break of 250%, and a water vapor permeability of 70 g / (m²·24h). The degradation rate within 28 days under simulated composting conditions reached 92%. This film has higher strength and better barrier properties, and is suitable for packaging applications with higher requirements.
[0042] Example 3 This embodiment provides a bamboo film manufacturing process for special applications, which achieves a special balance of film performance by adjusting the raw material ratio and processing parameters. The bamboo film manufacturing process of this embodiment includes the following steps: (1) Preparation of bamboo powder: First, select 4-year-old bamboo and remove the bamboo nodes and bamboo skin. Secondly, cut the bamboo into small sections of 7.5 cm in length. Then, use a wood slicer to cut the small sections into thin slices with a thickness of 2 mm. Thirdly, dry them at 70°C for 10 hours to reduce the moisture content to 6.5%. Finally, use a high-speed crusher to crush them and pass them through a 2000-mesh sieve to obtain bamboo powder with an average particle size of 7.5 μm.
[0043] In the embodiment of the present invention, 4-year-old bamboo provides a good balance between cellulose content and processing performance. The particle size of 7.5 μm ensures uniformity of the film while retaining a certain fiber structure, which is beneficial to enhancing the toughness of the film.
[0044] (2) Preparation of biodegradable excipients: In a reaction kettle, the following steps are performed: First, 20 parts by weight of polylactic acid (PLA, number average molecular weight of 100,000 g / mol, melting point of 160°C, glass transition temperature of 60°C) and 15 parts by weight of polycaprolactone (PCL, number average molecular weight of 80,000 g / mol, melting point of 62°C, glass transition temperature of -62°C) are added. Next, the temperature is raised to 175°C, the stirring speed is set to 125 rpm, and the mixture is kept for 35 minutes to completely melt. Then, the temperature is lowered to 145°C, 3.5 parts by weight of glycerol is added, and stirring is continued for 12 minutes. Finally, 4 parts by weight of triethyl citrate is added and stirred for 17 minutes to allow it to be fully mixed. The mixture is cooled to room temperature and pelletized to obtain biodegradable excipient particles.
[0045] In this example, the ratio and molecular weight of PLA and PCL were carefully adjusted to achieve the best balance of strength and flexibility. The amounts of glycerol and triethyl citrate were also optimized to ensure good processing properties and compatibility of the bamboo fiber-polymer interface.
[0046] (3) Mixed extrusion: 60 parts by weight of bamboo powder and 40 parts by weight of biodegradable auxiliary material particles are added to the feed port of the twin-screw extruder. The temperature distribution of the extruder from the feed section to the discharge section is: 110°C, 120°C, 130°C, 140°C, 150°C, 160°C. The screw speed is set to 90rpm and the extrusion pressure is controlled to 12.5MPa. The material stays in the extruder for 4 minutes.
[0047] (4) Film blowing: The melt extruded from the die head immediately enters the film blowing machine. The parameters of the film blowing process are set as follows: die head temperature is 165°C, cooling ring temperature is 17.5°C, blow-up ratio is 3.0, and pulling speed is 12.5 m / min.
[0048] (5) Cooling and stretching: The film passes through a multi-roll cooling system, and the temperature of the cooling roll is set at 35°C. The cooled film passes through a traction roll with a stretch ratio of 1.35.
[0049] (6) Winding: Finally, the film is wound up by the winding device, and the winding tension is controlled at 25N.
[0050] (7) Post-processing: The rolled film is stored in a constant temperature and humidity chamber for 36 hours at a temperature of 24°C and a relative humidity of 52.5%. Then, the film is slit into the required width using a precision slitting machine, and the slitting speed is controlled at 65 m / min. Finally, it is packaged in a clean environment and sealed with an antistatic polyethylene bag.
[0051] The bamboo film prepared by the above process has a thickness of 35μm, a tensile strength of 30 MPa, an elongation at break of 235%, and a water vapor permeability of 80 g / (m²·24h). The degradation rate within 28 days under simulated composting conditions reached 93.5%. This film achieves a good balance between strength, flexibility and barrier properties and is suitable for a variety of packaging applications, especially food packaging that requires a certain degree of flexibility.
[0052] Example 4 This embodiment provides a high-performance bamboo film production process, which achieves comprehensive improvement of film performance by optimizing raw material ratios and processing parameters. The bamboo film production process of this embodiment includes the following steps: (1) Preparation of bamboo powder: First, select 4.5-year-old bamboo and remove the bamboo nodes and bamboo skin. Secondly, cut the bamboo into small segments of 8 cm in length. Then, use a wood slicer to cut the small segments into thin slices with a thickness of 2.5 mm. Thirdly, dry them at 75°C for 11 hours to reduce the moisture content to 7%. Finally, use a high-speed grinder to crush them and pass them through a 2100 mesh sieve to obtain bamboo powder with an average particle size of 6 μm.
[0053] In the embodiment of the present invention, the 4.5-year-old bamboo provides a high cellulose content and a good fiber length distribution, which is conducive to improving the strength and toughness of the film. The particle size of 6 μm ensures the uniformity of the film while retaining the appropriate fiber structure, which helps to enhance the overall performance of the film.
[0054] (2) Preparation of biodegradable excipients: In a reaction kettle, the following steps are performed: First, 22 parts by weight of polylactic acid (PLA, number average molecular weight of 110,000 g / mol, melting point of 165°C, glass transition temperature of 62°C) and 18 parts by weight of polycaprolactone (PCL, number average molecular weight of 85,000 g / mol, melting point of 63°C, glass transition temperature of -63°C) are added. Next, the temperature is raised to 178°C, the stirring speed is set to 135 rpm, and the mixture is kept for 38 minutes to allow it to be completely melted. Then, the temperature is lowered to 148°C, 4 parts by weight of glycerol is added, and stirring is continued for 13 minutes. Finally, 4.5 parts by weight of triethyl citrate is added and stirred for 18 minutes to allow it to be fully mixed. The mixture is cooled to room temperature and pelletized to obtain biodegradable excipient particles.
[0055] In this example, the ratio and molecular weight of PLA and PCL were carefully adjusted to achieve high strength, high flexibility and good processing performance. The increased amount of glycerol and triethyl citrate further improved the flexibility and compatibility of the material, which helped to improve the overall performance of the film.
[0056] (3) Mixed extrusion: 55 parts by weight of bamboo powder and 45 parts by weight of biodegradable auxiliary material particles were added to the feed port of the twin-screw extruder. The temperature distribution of the extruder from the feed section to the discharge section was: 110°C, 120°C, 130°C, 140°C, 150°C, 160°C. The screw speed was set to 95 rpm and the extrusion pressure was controlled to 13 MPa. The material residence time in the extruder was 4.5 minutes.
[0057] (4) Film blowing: The melt extruded from the die head immediately enters the film blowing machine. The parameters of the film blowing process are set as follows: die head temperature is 168°C, cooling ring temperature is 18°C, blow-up ratio is 3.2, and pulling speed is 13 m / min.
[0058] (5) Cooling and stretching: The film passes through a multi-roll cooling system, and the temperature of the cooling roll is set at 37°C. The cooled film passes through a traction roll with a stretch ratio of 1.4.
[0059] (6) Winding: Finally, the film is wound up by the winding device, and the winding tension is controlled at 27N.
[0060] (7) Post-processing: The rolled film is stored in a constant temperature and humidity chamber for 40 hours at a temperature of 24.5°C and a relative humidity of 53%. Then, the film is slit into the required width using a precision slitting machine, and the slitting speed is controlled at 70 m / min. Finally, it is packaged in a clean environment and sealed with an antistatic polyethylene bag.
[0061] The bamboo film prepared by the above process has a thickness of 40μm, a tensile strength of 33 MPa, an elongation at break of 240%, and a water vapor permeability of 75 g / (m²·24h). The degradation rate within 28 days under simulated composting conditions reached 94%. This film achieves an excellent balance between strength, flexibility, barrier properties and biodegradability, and is suitable for high-end packaging applications such as food packaging, medical supplies packaging, etc.
[0062] In summary, the present invention demonstrates the various possibilities and flexibility of bamboo film manufacturing process through four embodiments. By adjusting the preparation parameters of bamboo powder, the composition of biodegradable auxiliary materials and processing conditions, bamboo films with different performance characteristics can be obtained to meet various application requirements. It is worth noting that the bamboo film of the present invention not only has excellent mechanical properties and barrier properties, but also maintains good biodegradability, which is a feature not possessed by traditional plastic films.
[0063] In the present invention, bamboo powder is used as the main raw material, which not only makes full use of renewable resources, but also provides unique mechanical properties and biodegradable characteristics for the film. The careful design and optimization of biodegradable auxiliary materials further enhance the overall performance of the film, especially in terms of flexibility and processability. The addition of glycerol as a plasticizer effectively improves the flexibility of the film, while the addition of triethyl citrate significantly improves the compatibility of bamboo fiber with the polymer matrix, thereby enhancing the uniformity and overall performance of the film. In addition, in the preparation process of the present invention, further optimization of film performance is achieved by accurately controlling process parameters such as extrusion, film blowing, cooling and stretching. This comprehensive process control not only ensures the consistency of product quality, but also provides the possibility for customization of film performance.
[0064] In general, the bamboo film manufacturing process provided by the present invention not only fills the gap in the application of bamboo in the film field, but also provides a new idea and solution for solving the problem of plastic pollution. This environmentally friendly film material is expected to be widely used in packaging, agricultural covering and other fields, making an important contribution to achieving sustainable development and carbon neutrality goals.
[0065] Comparative Example 1 This comparative example provides a process for making a biodegradable film without bamboo powder, which is used to compare with Example 1 to verify the key role of bamboo powder in the film performance. The process includes the following steps: (1) Preparation of biodegradable excipients: First, add 45 parts by weight of polylactic acid (PLA, number average molecular weight of 80,000 g / mol, melting point of 150°C, glass transition temperature of 55°C) and 30 parts by weight of polycaprolactone (PCL, number average molecular weight of 70,000 g / mol, melting point of 58°C, glass transition temperature of -60°C) into a reactor. Next, raise the temperature to 170°C, set the stirring speed to 100 rpm, and keep it for 30 minutes to allow it to melt completely. Then, lower the temperature to 140°C, add 20 parts by weight of glycerol, and continue stirring for 10 minutes. Finally, add 5 parts by weight of triethyl citrate and stir for 15 minutes to allow it to be fully mixed. Cool the mixture to room temperature and pelletize it to obtain biodegradable excipient particles.
[0066] (2) Mixed extrusion: Add the prepared biodegradable auxiliary material particles directly to the feed port of the twin-screw extruder. The temperature distribution of the extruder from the feed section to the discharge section is: 110℃, 120℃, 130℃, 140℃, 150℃, 160℃. Set the screw speed to 80rpm and control the extrusion pressure to 10MPa. The material stays in the extruder for 3 minutes.
[0067] (3) Film blowing, cooling and stretching, winding, and post-processing: These steps are the same as those in Example 1.
[0068] The film prepared by the above process has a thickness of 20μm, a tensile strength of 18 MPa, an elongation at break of 180%, and a water vapor permeability of 110 g / (m²·24h). The degradation rate within 28 days under simulated composting conditions reached 98%.
[0069] Comparative analysis: Compared with Example 1, the mechanical properties and barrier properties of the film in this comparative example are significantly reduced, which confirms the key role of bamboo powder in enhancing the performance of the film. The cellulose structure in bamboo powder not only provides mechanical strength, but also forms a complex network structure through interaction with the polymer matrix, thereby improving the overall performance of the film.
[0070] Comparative Example 2 This comparative example provides a film production process containing only bamboo powder and PLA, which is used to compare with Example 2 to verify the role of PCL, glycerol and triethyl citrate in optimizing film performance. The process includes the following steps: (1) Preparation of bamboo powder: Same as Example 2.
[0071] (2) Preparation of biodegradable excipients: In a reactor, add only 50 parts by weight of polylactic acid (PLA, number average molecular weight 120,000 g / mol, melting point 170°C, glass transition temperature 65°C). Raise the temperature to 180°C, set the stirring speed to 150 rpm, and maintain for 40 minutes to allow complete melting. Cool the mixture to room temperature and pelletize to obtain biodegradable excipient particles.
[0072] (3) Mixing and extrusion, film blowing, cooling and stretching, winding, and post-processing: These steps are the same as those in Example 2.
[0073] The film prepared by the above process has a thickness of 50μm, a tensile strength of 40 MPa, an elongation at break of 150%, and a water vapor permeability of 60 g / (m²·24h). The degradation rate within 28 days under simulated composting conditions reaches 85%.
[0074] Comparative analysis: Compared with Example 2, the tensile strength of the film in this comparative example is slightly higher, but the elongation at break is significantly reduced, indicating that the film has become more brittle. This confirms the important role of PCL in improving the flexibility of the film. At the same time, the lack of glycerol and triethyl citrate leads to a decrease in the processing performance of the film, which reflects the key role of these two additives in improving the fluidity and compatibility of the material.
[0075] Comparative Example 3 This comparative example provides a process for making a film with too high a content of bamboo powder, which is used to compare with Example 3 to verify the influence of the raw material ratio on the film performance. The process includes the following steps: (1) Preparation of bamboo powder: Same as Example 3.
[0076] (2) Preparation of biodegradable excipients: Same as Example 3.
[0077] (3) Mixed extrusion: 80 parts by weight of bamboo powder and 20 parts by weight of biodegradable auxiliary material particles were added to the feed port of a twin-screw extruder. Other parameters were the same as those in Example 3.
[0078] (4) Film blowing, cooling and stretching, winding, and post-processing: These steps are the same as those in Example 3.
[0079] The film prepared by the above process has a thickness of 35μm, a tensile strength of 20 MPa, an elongation at break of 120%, and a water vapor permeability of 95 g / (m²·24h). The degradation rate within 28 days under simulated composting conditions reaches 97%.
[0080] Comparative analysis: Compared with Example 3, the mechanical properties of the film in this comparative example are significantly reduced, and the barrier properties are also reduced. This shows that the excessively high bamboo powder content leads to insufficient polymer matrix in the film, which cannot fully exert the bonding effect, thereby affecting the overall performance of the film. This verifies the rationality and importance of the raw material ratio in the present invention.
[0081] Comparative Example 4 This comparative example provides a film production process without glycerol, which is used to compare with Example 4 to verify the importance of glycerol as a plasticizer. The process includes the following steps: (1) Preparation of bamboo powder: Same as Example 4.
[0082] (2) Preparation of biodegradable excipients: In a reaction kettle, the following steps are performed: First, 24 parts by weight of polylactic acid (PLA, number average molecular weight of 110,000 g / mol, melting point of 165°C, glass transition temperature of 62°C) and 20 parts by weight of polycaprolactone (PCL, number average molecular weight of 85,000 g / mol, melting point of 63°C, glass transition temperature of -63°C) are added. Next, the temperature is raised to 178°C, the stirring speed is set to 135 rpm, and the mixture is kept for 38 minutes to allow it to be completely melted. Finally, 4.5 parts by weight of triethyl citrate is added and stirred for 18 minutes to allow it to be fully mixed. The mixture is cooled to room temperature and pelletized to obtain biodegradable excipient particles.
[0083] (3) Mixing and extrusion, film blowing, cooling and stretching, winding, and post-processing: These steps are the same as those in Example 4.
[0084] The film prepared by the above process has a thickness of 40μm, a tensile strength of 38 MPa, an elongation at break of 180%, and a water vapor permeability of 70 g / (m²·24h). The degradation rate within 28 days under simulated composting conditions reached 92%.
[0085] Comparative analysis: Compared with Example 4, the tensile strength of the film in this comparative example is slightly higher, but the elongation at break is significantly reduced. This confirms the important role of glycerol as a plasticizer in improving the flexibility of the film. At the same time, the lack of glycerol also leads to a decrease in the processing performance of the film, which reflects the key role of plasticizers in improving the fluidity of materials.
[0086] Comparative Example 5 This comparative example provides a film production process using PLA and PCL with different molecular weights, which is used to compare with Example 1 to verify the effect of polymer molecular weight on film performance. The process includes the following steps: (1) Preparation of bamboo powder: Same as in Example 1.
[0087] (2) Preparation of biodegradable excipients: In a reaction kettle, the following steps were performed: First, 15 parts by weight of polylactic acid (PLA, number average molecular weight of 50,000 g / mol, melting point of 145°C, glass transition temperature of 50°C) and 10 parts by weight of polycaprolactone (PCL, number average molecular weight of 50,000 g / mol, melting point of 55°C, glass transition temperature of -65°C) were added. The other steps were the same as those in Example 1.
[0088] (3) Mixing and extrusion, film blowing, cooling and stretching, winding, and post-processing: These steps are the same as those in Example 1.
[0089] The film prepared by the above process has a thickness of 20 μm, a tensile strength of 22 MPa, an elongation at break of 200%, and a water vapor permeability of 100 g / (m²·24h). The degradation rate within 28 days under simulated composting conditions reaches 98%.
[0090] Comparative analysis: Compared with Example 1, the mechanical properties and barrier properties of the film in this comparative example are reduced. This confirms the importance of high molecular weight PLA and PCL in improving film performance. Although lower molecular weight polymers may be beneficial to improving the flexibility and processability of the film, they also reduce the strength and barrier properties of the film.
[0091] Comparative Example 6 This comparative example provides a film production process without triethyl citrate, which is used to compare with Example 2 to verify the effect of triethyl citrate in improving material compatibility. The process includes the following steps: (1) Preparation of bamboo powder: Same as Example 2.
[0092] (2) Preparation of biodegradable excipients: In a reaction kettle, the following steps are performed: First, 25 parts by weight of polylactic acid (PLA, number average molecular weight of 120,000 g / mol, melting point of 170°C, glass transition temperature of 65°C) and 20 parts by weight of polycaprolactone (PCL, number average molecular weight of 90,000 g / mol, melting point of 65°C, glass transition temperature of -65°C) are added. Next, the temperature is raised to 180°C, the stirring speed is set to 150 rpm, and maintained for 40 minutes to allow complete melting. Then, the temperature is lowered to 150°C, 5 parts by weight of glycerol is added, and stirring is continued for 15 minutes. The mixture is cooled to room temperature and pelletized to obtain biodegradable excipient particles.
[0093] (3) Mixing and extrusion, film blowing, cooling and stretching, winding, and post-processing: These steps are the same as those in Example 2.
[0094] The film prepared by the above process has a thickness of 50μm, a tensile strength of 32 MPa, an elongation at break of 230%, and a water vapor permeability of 75 g / (m²·24h). The degradation rate within 28 days under simulated composting conditions reached 93%.
[0095] Comparative analysis: Compared with Example 2, the mechanical properties of the film in this comparative example are slightly reduced, especially the reduction in tensile strength is more obvious. This confirms the important role of triethyl citrate in improving the compatibility of bamboo powder with the polymer matrix. The lack of triethyl citrate leads to insufficient interface bonding, thereby affecting the overall performance of the film. At the same time, the uniformity of the film is also reduced, which further illustrates the key role of triethyl citrate in promoting the full mixing of the components.
[0096] Through these six comparative examples, the present invention systematically verifies the importance of each key component and process parameter in the present invention. As the main filling material, bamboo powder not only provides good mechanical properties, but also gives the film unique biodegradability. The synergistic effect of PLA and PCL achieves a balance between film strength and flexibility. Glycerol as a plasticizer significantly improves the processing performance and flexibility of the film. Triethyl citrate plays a key role in improving the compatibility of components. The synergistic effect of these components, coupled with the optimized process parameters, together constitute the core innovation of the present invention, so that the prepared bamboo film has reached a high level in mechanical properties, barrier properties and biodegradability. This series of comparative experiments fully demonstrates the creativity and superiority of the present invention, and provides strong support for its application in the field of environmentally friendly packaging materials.
[0097] In order to comprehensively evaluate the effectiveness and superiority of the process of the present invention, the present invention has designed a series of test experiments covering the mechanical properties, thermal properties, barrier properties, biodegradability and microstructural characteristics of the film. These tests can not only verify the core innovation of the present invention, but also deeply explore the synergistic mechanism between the components.
[0098] First, the present invention conducted a mechanical property test. A universal testing machine (model: Instron 5967) was used to test according to ASTM D882 standard. The film was cut into strip samples with a width of 10 mm and a length of 100 mm. The test speed was set to 50 mm / min, the test environment temperature was 23±2°C, and the relative humidity was 50±5%. Each sample was tested 5 times and the average value was taken.
[0099] Secondly, the present invention analyzes the thermal properties of the film. The melting temperature (Tm) and glass transition temperature (Tg) of the film were measured using a differential scanning calorimeter (DSC, model: TAInstruments Q2000). The test conditions were: in a nitrogen atmosphere, the temperature was increased from -80°C to 200°C at a rate of 10°C / min, then cooled to -80°C at the same rate, and then heated to 200°C at a rate of 10°C / min again. Tm and Tg data were obtained from the second heating curve.
[0100] Then, the present invention evaluates the barrier properties of the film. The water vapor transmission rate (WVTR) test adopts the ASTM E96 standard, using a water vapor transmission rate tester (model: Permatran-W 3 / 33) at 38°C and 90% relative humidity. The oxygen transmission rate (OTR) test adopts the ASTM D3985 standard, using an oxygen transmission rate tester (model: Ox-Tran2 / 21) at 23°C and 0% relative humidity.
[0101] Again, the present invention conducted a biodegradability test. According to ISO 14855-1 standard, the biodegradability of the film was tested under simulated composting conditions (58±2°C, relative humidity 50±5%). The CO2 production was measured every 7 days and the degradation rate was calculated.
[0102] Finally, in order to gain a deeper understanding of the microstructure of the film, the present invention uses a scanning electron microscope (SEM, model: JEOL JSM-7800F) to observe the cross-sectional morphology of the film. After the sample is fractured by liquid nitrogen, the surface is treated with gold spraying, and the acceleration voltage is 5 kV.
[0103] Table 1. Test results of mechanical properties and barrier properties of bamboo films
[0104] Table 2. Thermal properties and biodegradability test results of bamboo films
[0105] Based on the above test results, the present invention can draw the following conclusions: 1. Mechanical properties: Example 2 exhibits the best comprehensive mechanical properties, with a tensile strength of 35.2 MPa, an elongation at break of 250%, and an elastic modulus of 2.2 GPa. This excellent mechanical property is attributed to the synergistic effect of bamboo powder, PLA, and PCL. Bamboo powder provides a good reinforcement effect, while the optimized ratio of PLA and PCL achieves a balance between strength and toughness.
[0106] 2. Barrier performance: Example 2 also showed the best barrier performance, with a WVTR of 70 g / m²·day and an OTR of 120 cm³ / m²·day. This excellent barrier performance may be due to the dense interface structure formed between the bamboo powder and the polymer matrix, which effectively reduces the permeation of gas molecules.
[0107] 3. Thermal properties: The Tm and Tg of Example 2 are 168°C and 63°C, respectively, showing good thermal stability. This improvement in thermal properties may be due to the fact that the addition of bamboo powder increases the crystallinity of the material, while the synergistic effect of PLA and PCL also improves the overall thermal stability.
[0108] 4. Biodegradability: All examples showed good biodegradability, with degradation rates exceeding 90% within 28 days, which proves that the present invention successfully achieved the biodegradability of the material while maintaining good performance.
[0109] 5. Microstructure: SEM observation results show that the cross-sectional morphology of Example 2 is the most uniform, and the interface between the bamboo powder and the polymer matrix is well bonded, and almost no obvious interface separation is observed. This excellent interface bonding may be due to the addition of triethyl citrate, which effectively improves the compatibility between the components.
[0110] The biggest highlight of the present invention is that it achieves a perfect balance between performance and environmental protection. Through the exquisite proportion of bamboo powder, PLA, PCL and additives, the present invention obtains a new type of film material that has excellent mechanical properties and barrier properties and is rapidly biodegradable. It is particularly noteworthy that the present invention has demonstrated some unexpected technical effects: 1. Synergistic enhancement effect: The bamboo powder and PLA / PCL blend system showed an unexpected improvement in mechanical properties. This may be due to the special interface structure formed between the cellulose in the bamboo powder and PLA / PCL, which not only improved the strength of the material, but also improved its toughness.
[0111] 2. Selective barrier properties: The film of the present invention exhibits different degrees of barrier effects on water vapor and oxygen, and this selective barrier property is of great significance in the field of food packaging. This may be because the addition of bamboo powder changes the arrangement of polymer chains and forms a special microscopic channel structure.
[0112] 3. Accelerated biodegradation: Despite the addition of bamboo powder, the biodegradation rate of the film did not decrease significantly, but in some cases it slightly increased. This may be because bamboo powder provides an additional nutrient source for microorganisms, accelerating the degradation process.
[0113] 4. Improved thermal stability: The addition of bamboo powder not only did not reduce the thermal stability of the material, but in some cases slightly improved it. This is because some components in bamboo powder (such as lignin and bamboo flavonoids) have antioxidant properties, which improve the stability of the material at high temperatures.
[0114] 5. Optimization of processing properties: Despite the addition of a large amount of bamboo powder, the material still maintains good processing properties. This may be due to the synergistic effect of glycerol and triethyl citrate, which not only improves the compatibility between components but also optimizes the rheological properties of the material.
[0115] In summary, the present invention realizes a biodegradable film with excellent comprehensive performance through ingenious formula design and process optimization. This film not only performs well in mechanical properties, barrier properties and thermal stability, but also maintains the characteristics of rapid biodegradation. These characteristics make the film material of the present invention have broad application prospects in the fields of food packaging, agricultural covering, etc., and provide an innovative solution to the problem of plastic pollution.
[0116] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A bamboo film production process, characterized in that: The following steps are involved: (1) preparing bamboo powder; (2) preparing biodegradable auxiliary materials; (3) mixing and extruding the bamboo powder and the biodegradable auxiliary materials; (4) performing film blowing on the extrudate; (5) cooling and stretching the formed film; (6) winding the stretched film; and (7) performing post-treatment on the wound film.
2. The bamboo film manufacturing process according to claim 1, characterized in that: The step (1) comprises: First, select 3-5 year old bamboo and remove the bamboo nodes and bamboo skin; Secondly, cut the bamboo into small pieces of 5-10cm in length; Then, use a wood slicer to cut the small segments into slices with a thickness of 1-3 mm; Next, dry at 60-80℃ for 8-12 hours to reduce the moisture content to 5-8%; Finally, the powder was crushed by a high-speed crusher and passed through a 1800-2200 mesh sieve to obtain bamboo powder with an average particle size of 5-10 μm.
3. The bamboo film manufacturing process according to claim 1, characterized in that: The step (2) comprises: (a) Add the following raw materials into the reactor in sequence: Polylactic acid (PLA) 15-25 parts by weight, Polycaprolactone (PCL) 10-20 parts by weight, 2-5 parts by weight of glycerol, 3-5 parts by weight of triethyl citrate; (b) First, PLA and PCL were heated to 170-180°C, stirred at 100-150 rpm, and maintained for 30-40 minutes; (c) Next, cool to 140-150°C, add glycerol, and continue stirring for 10-15 minutes; (d) then adding triethyl citrate and stirring for 15-20 minutes; (e) finally cooling the mixture to room temperature and dicing to obtain biodegradable excipient granules.
4. The bamboo film manufacturing process according to claim 1, characterized in that: The step (3) comprises: Add 50-70 parts by weight of bamboo powder and 30-50 parts by weight of biodegradable auxiliary material particles into the feed port of a twin-screw extruder. Among them, the temperature distribution of the extruder from the feeding section to the discharging section is: 110℃, 120℃, 130℃, 140℃, 150℃, 160℃, The screw speed is set to 80-100rpm, The extrusion pressure is controlled at 10-15MPa. The material stays in the extruder for 3-5 minutes.
5. The bamboo film manufacturing process according to claim 1, characterized in that: The film blowing process parameters of step (4) include: die head temperature: 160-170° C., cooling ring temperature: 15-20° C., blow-up ratio: 2.5-3.5, and pulling speed: 10-15 m / min.
6. The bamboo film manufacturing process according to claim 1, characterized in that: The step (5) comprises: Use a multi-roll cooling system with a cooling roller temperature of 30-40°C. The cooled film passes through a traction roller with a stretch ratio of 1.2-1.
5.
7. The bamboo film manufacturing process according to claim 1, characterized in that: The step (7) comprises: (a) Store the rolled film in a constant temperature and humidity chamber for 24-48 hours at a temperature of 23±2°C and a relative humidity of 50±5%; (b) Use a precision slitting machine to slit the film into the required width, and the slitting speed is controlled at 50-80 m / min; (c) Packaging the slit films.
8. The bamboo film manufacturing process according to any one of claims 1 to 7, characterized in that: The polylactic acid PLA in the biodegradable auxiliary material has the following characteristics: Number average molecular weight Mn: 80,000-120,000 g / mol, Melting point: 150-170℃, Glass transition temperature Tg: 55-65℃.
9. The bamboo film manufacturing process according to any one of claims 1 to 7, characterized in that: The polycaprolactone PCL in the biodegradable excipient has the following characteristics: Number average molecular weight Mn: 70,000-90,000 g / mol, Melting point: 58-65℃, Glass transition temperature Tg: -60 to -65°C.
10. The bamboo film manufacturing process according to any one of claims 1 to 7, characterized in that: It also includes quality control of the produced film, including: Test the film thickness, control it within the range of 20-50μm, and the thickness deviation shall not exceed ±5%; The tensile strength of the tested film should be no less than 20 MPa; The elongation at break of the test film should not be less than 200%; The water vapor transmission rate of the test film should not be higher than 100 g / (m²·24h); Conduct biodegradability tests and the degradation rate should reach more than 90% within 28 days under simulated composting conditions.
Citation Information
Cited By
Preparation method of bamboo-based cellulose degradable plastic film containing modified PLA
CN121181958A